2008
DOI: 10.1001/archinte.168.5.501
|View full text |Cite
|
Sign up to set email alerts
|

Geographic Variation and Risk of Skin Cancer in US Women<subtitle>Differences Between Melanoma, Squamous Cell Carcinoma, and Basal Cell Carcinoma</subtitle>

Abstract: Background: Occurrences of melanoma, squamous cell carcinoma (SCC), and basal cell carcinoma (BCC) have been associated with varying geography. Our goal was to evaluate differences in risk of these skin cancers according to residence at varying UV indices at 3 time points.Methods: Prospective 1984-2002 study of 84 836 female nurses who lived in different UV index regions of the United States at birth and at 15 or 30 years of age. The outcome measure was diagnosis of melanoma, SCC, or BCC. Results:During the 18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
66
5
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 81 publications
(80 citation statements)
references
References 58 publications
7
66
5
2
Order By: Relevance
“…Despite the progresses in chemotherapy, surgery, and radiotherapy to limit the mortality it causes, the situation is still not optimistic because melanoma incidence has doubled since 1950s in Europe, Singapore, Canada, and United State [2][3][4]. Consequently, the further research of melanoma, such as the mechanisms underlying its pathogenesis, is important to identify its occurrence and metastasis early and provide new potential targets for melanoma treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the progresses in chemotherapy, surgery, and radiotherapy to limit the mortality it causes, the situation is still not optimistic because melanoma incidence has doubled since 1950s in Europe, Singapore, Canada, and United State [2][3][4]. Consequently, the further research of melanoma, such as the mechanisms underlying its pathogenesis, is important to identify its occurrence and metastasis early and provide new potential targets for melanoma treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The increased melanin barrier in darker-pigmented individuals decreases both ultraviolet (UV) A and B radiation through the skin (38)(39)(40). UV radiation is known to induce both cell death and malignant transformation of skin cells; it is considered the paramount risk factor for melanoma (41)(42)(43)(44)(45)(46). Compared to fairer-skinned people, UVB radiation through the epidermis is diminished by approximately 50% in darker-skinned people (38), and UVA transmission through the dermis decreases from 27 to 4% at 314 nm and 47 to 14% at 400 nm (39).…”
Section: Ethnicitymentioning
confidence: 99%
“…In sheep, the tumor occurs most frequently on the muzzle, lips, eyelids, pinnae, perineum and vulva (MAULDIN & KENNEDY, 2016;MACEDO et al, 2008). While SCC in animals and humans is global in occurrence, differences in its distribution in various areas of García et al the world have been observed (NEWTON, 1996;BRONDEN et al, 2007;QURESHI et al, 2008). The incidence rate of SCC varies geographically, and is highest in the southern hemisphere and with decreasing latitude, i.e.…”
Section: Introductionmentioning
confidence: 99%